THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT PT. HADJI KALLA TOYOTA ALAUDDIN BRANCH MAKASSAR CITY - Nurul Hikmah Nirwan; Aulia, Aulia; Sherry Edelia Natsir Kalla (CV. AFDIFAL MAJU BERKAH, 2024)
The research is aimed at describing: Testing the Effect of Service Quality on Customer Satisfaction at PT. Hadji Kalla Toyota Alauddin Branch, Makassar City. The population in this research is consumers at PT. Hadji Kalla Toyota Alauddin Branch, Makassar City, totaling 1,400 consumers, used the Slovin formula to determine the number of samples, namely 93 respondents. It is known that the significant value in this research is the influence of service quality (X) on consumer satisfaction (Y) of 0.001 < 0.05, and the calculated value is 18, 593 > table value 1, 986. The type of data used in this research is quantitative. obtained from questionnaires distributed to respondents. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert Scale method. Based on the results of research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 29 application regarding the influence of service quality on consumer satisfaction, it shows that service quality has a positive and significant effect on consumer satisfaction.